Eustathius of Antioch and a Fragment Attributed to Patriarch Photius - Antōnopulu, Theodōra (The journal of theological studies, 2006)
This article deals with the fragment on Hebr. 7:3 attributed to Patriarch Photius of Constantinople (ninth century) as part of his commentary on the Pauline epistles. It shows that the fragment is an excerpt from the Epistula ad Alexandrum Alexandrinum (De Melchisedech) of the Nicene Father Eustathius of Antioch, and examines its relation to the Photian commentary as well as its provenance and importance for the transmission of Eustathius’ work.